Human papillomavirus vaccinations at recommended ages: How a middle school-based educational and vaccination program increased uptake in the Rio Grande Valley. Issue 6 (30th November 2022) - Rodriguez, Ana M.; Do, Thuy Quynh N.; Chen, Lu; Schmeler, Kathleen M.; Montealegre, Jane R.; Kuo, Yong-Fang
ABSTRACT: Human papillomavirus (HPV) vaccination is recommended for U.S. adolescents at ages 11–12 requiring two or three doses depending on if the vaccine series started before age 15. The objective was to compare HPV vaccination rates among medically underserved, economically disadvantaged, students in rural middle school districts (Rio Grande Valley [RGV], Texas) by age of initiation (≤ age 11 years vs. age 12 years and older). This quasi-experimental study included 1, 766 students (884 females; 882 males) who received at least one HPV vaccine dose through our school-based vaccination program between 08/2016-06/2022. Summary statistics were stratified by age at initiation and gender. The overall HPV up-to-date (UTD) rate was 59.7% (95% Confidence Interval: 57.4–62.0%). The median age at HPV UTD (range) was 12 years (9–19) and median interval between HPV vaccine doses (range) was 316 days (150–2, 855). Most students received the HPV vaccine bundled with other vaccinations (72.4%, 1, 279/1, 766). There was a higher HPV UTD rate among students who initiated the HPV vaccine on or before age 11 than those who initiated on or after age 12 (73.6% versus 45.1%, respectively). The median age of HPV UTD was age 12 for those initiating on or before 11 years versus age 13 for those initiating on or after 12 years of age. Initiating the HPV vaccine at age ≤11 years increased completion of the HPV vaccine series. Improving HPV vaccine coverage and introduction of pan-gender vaccination programs will significantly decrease HPV-related diseases in the RGV.